Peroxisome Proliferator-Activated Receptors in Regulation of Cytochromes P450: New Way to Overcome Multidrug Resistance?. (21st October 2012) - Cizkova, Katerina; Konieczna, Anna; Erdosova, Bela; Lichnovska, Radka; Ehrmann, Jiri
Abstract : Embryonic and tumour cells are able to protect themselves against various harmful compounds. In human pathology, this phenomenon exists in the form of multidrug resistance (MDR) that significantly deteriorates success of anticancer treatment. Cytochromes P450 (CYPs) play one of the key roles in the xenobiotic metabolism. CYP expression could contribute to resistance of cancer cells to chemotherapy. CYP epoxygenases (CYP2C and CYP2J) metabolize about 20% of clinically important drugs. Besides of drug metabolism, CYP epoxygenases and their metabolites play important role in embryos, normal body function, and tumors. They participate in angiogenesis, mitogenesis, and cell signaling. It was found that CYP epoxygenases are affected by peroxisome proliferator-activated receptor α (PPAR α ). Based on the results of current studies, we assume that PPARs ligands may regulate CYP2C and CYP2J and in some extent they may contribute to overcoming of MDR in patients with different types of tumours.